Effects of freezing and thawing in embankment dams - Jantzer, Isabel; Knutsson, Sven (Luleå tekniska universitet, Geoteknologi, 2007)
Embankment dams located in cold climate are subjected to freezing condition, which is usually not taken into account in the design. Frost susceptible fill material may be exposed to frost action, a process known for ice lens formation which increases water content and soil volume. Upon thawing, rearrangement of particles takes place and the soil structure is altered. Fine grained soils may therefore exhibit weak zones with reduced shear strength and increased hydraulic conductivity. Internal erosion may start in such weak zones, thus causing problems for the dam construction. Therefore, climate should be considered in order to find temperature distribution and pore pressures in the embankment. A study of freezing effects has been carried out at the Suorva hydropower embankment dam in northern Sweden. The study included field investigations, i.e. test pit excavation, where weak zones have been observed. The comparison of results to those from temperature calculations with a commercial finite element program showed that the core is exposed to frost action, thus causing seepage problems. Godkänd; 2007; 20090814 (svek)